Evidence and leading indicators of change success. Issue 10 (14th September 2015) - Arnold, Paul
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper discusses the important issues relating to the management of corporate change and includes an appropriate case study. It will benefit all business leaders, particularly those involved with the development of change strategies and the implementation of those strategies. Paul Arnold's experience will improve their understanding of change management by providing the tools that will enable them to effectively understand and assess the progress of change initiatives in their organization. Findings – Every organization is subject to change, and virtually, everyone within the organization will be affected by change. Such is the impact of a rapidly evolving marketplace that organizational change management has become a permanent feature of the business landscape. To be effective, organizational change must be able to genuinely transform the business. Yet in the relentless search for new techniques to revolutionize the way things are done, and in the haste to manage technological discontinuities, many organizations fail to adequately develop, communicate and execute their vision for the change. Originality/value – The recently developed Change Index discussed in this paper provides a concrete and clear measurement system that enables management to effectively understand and assess progress of change initiatives in their organization. The paper benefits all business leaders, particularly those involved with the development of change strategies and the implementation of those strategies.